2022
DOI: 10.1111/jbi.14315
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of unique and asynchronous population dynamics in Malagasy herpetofauna

Abstract: Aim: A long history of isolation coupled with complex landscapes makes Madagascar ideal for exploring the historical factors that have shaped patterns of population diversity and endemism. Many species-level studies have suggested Late Quaternary climate change may have influenced population dynamics in the tropics, but unique biomes and individual species properties may have driven idiosyncratic responses to these shifts. Here, we use community-scale population genetic data to investigate the impact of Quater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 109 publications
(212 reference statements)
0
8
0
Order By: Relevance
“…Madagascar has served as model to develop numerous hypotheses of diversification mechanisms (e.g. Colwell & Lees, 2000; Craul et al, 2007; Dewar & Richard, 2007; Goodman & Ganzhorn, 2004; Kuhn et al, 2022; Lees et al, 1999; Raxworthy & Nussbaum, 1995; Wilmé et al, 2006; Wollenberg Valero, 2015), as partially summarized in Vences et al (2009) and Brown et al (2014). Most of these studies were based on either patterns of species distributions, phylogenies, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Madagascar has served as model to develop numerous hypotheses of diversification mechanisms (e.g. Colwell & Lees, 2000; Craul et al, 2007; Dewar & Richard, 2007; Goodman & Ganzhorn, 2004; Kuhn et al, 2022; Lees et al, 1999; Raxworthy & Nussbaum, 1995; Wilmé et al, 2006; Wollenberg Valero, 2015), as partially summarized in Vences et al (2009) and Brown et al (2014). Most of these studies were based on either patterns of species distributions, phylogenies, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Body size is often used as a proxy of dispersal capability, with small bodied-animals presenting stronger responses to vicariant barriers (Wollenberg et al, 2011;Arteaga et al, 2016). Species-specific traits other than body size, such as habitat use, may also affect dispersal (Zamudio et al, 2016;Reid et al, 2019;Kuhn et al, 2021). For example, phylogenetic studies indicate a strong vicariant effect of the SFR on several species of limbless (or reduced-limb) fossorial squamate (Rodrigues, 1996;Rodrigues and Juncá, 2002; 10.3389/fevo.2022.983134 Siedchlag et al, 2010;Almeida et al, 2020), which likely have limited river-crossing abilities due to their underground lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that rates of diversification in the gemsnakes declined significantly over the entire tree during the Pleistocene (Kuhn et al, 2022 ). Since then, Louca and Pennell ( 2020 ) demonstrated that rates of speciation estimated from molecular phylogenies may be congruent with a wide range of diversification scenarios.…”
Section: Methodsmentioning
confidence: 96%